A study for changing aspects of water polo games due to the changes in international rules in 2005 - Shimizu, N.; Takagi, H. (Japanese Journal of Sciences in Swimming and Water Exercise, 2007)
The FINA (Federation Internationale de Natation Amateur) has changed the international rules of water polo to make the water polo more attractive globally in 2005. Although a major change was expected in aspects of the games by adopting the revised rules, a verification how changed has not been done yet. Therefore, the purpose of this study is to evaluate the aspects of the games such as swimming distance, swimming velocity and time-motion analysis under a revised condition. The activities of 18 water-polo-players (6 center forwards, 6 drivers and 6 center backs) were videotaped and analyzed, in a total of five games of the Japan Swimming Championship which was held in the Tokyo Metropolitan Gymnasium from 29th June to 1st July in 2007. A two-dimensional DLT method was used to evaluate a position of player, swimming distance and swimming velocity by the Fame Dias II (DKH Cooperation). In addition the time-motion analysis was done to evaluate the game qualitatively. As results, an average of game duration was 48min 53second. An average of swimming distance of total is 1803.3 ± 137.8m. An average of swimming velocity of total is 0.65 ± 0.06m/s. It is revealed that the mean duration of contact was decreased, the mean duration of swimming was increased and the mean duration of vertical position was decreased. These results show that the intention with the revision of rules has been achieved.